The Evolution of Blood Transfusion in the Trauma Patient: Whole Blood Has Come Full Circle - Black, Jonathan A.; Pierce, Virginia S.; Kerby, Jeffrey D.; Holcomb, John B. (Seminars in Thrombosis and Hemostasis, 2020)
Whole blood transfusion in the United States dates back to the Civil War, and it was widely used in all major conflicts since World War I. To understand our current civilian transfusion practices and to anticipate future changes in trauma resuscitation, it is important to understand the series of decisions that led trauma surgeons away from whole blood resuscitation and toward component therapy. In this review, we examine the historical basis for blood transfusion in trauma and examine the recent literature and future directions pertaining to blood product resuscitation in hemorrhaging patients.
Keywords: trauma; whole blood; blood products; transfusion; component therapy; balanced resuscitation